Gastrointestinal peptides and small-bowel hypomotility are possible causes for fasting and postprandial symptoms in active Crohn's disease. Issue 1 (26th September 2019) - Khalaf, Asseel; Hoad, Caroline L; Menys, Alex; Nowak, Adam; Radford, Shellie; Taylor, Stuart A; Latief, Khalid; Lingaya, Melanie; Falcone, Yirga; Singh, Gulzar; Spiller, Robin C; Gowland, Penny A; et al.
ABSTRACT: Background: Crohn's disease (CD) patients suffer postprandial aversive symptoms, which can lead to anorexia and malnutrition. Changes in the regulation of gut hormones and gut dysmotility are believed to play a role. Objectives: This study aimed to investigate small-bowel motility and gut peptide responses to a standard test meal in CD by using MRI. Methods: We studied 15 CD patients with active disease (age 36 ± 3 y; BMI 26 ± 1 kg/m 2 ) and 20 healthy volunteers (HVs; age 31 ± 3 years; BMI 24 ± 1 kg/m 2 ). They underwent baseline and postprandial MRI scans, symptom questionnaires, and blood sampling following a 400-g soup meal (204 kcal). Small-bowel motility, other MRI parameters, and glucagon-like peptide-1 (GLP-1), polypeptide YY (PYY), and cholecystokinin peptides were measured. Data are presented as means ± SEMs. Results: HVs had significantly higher fasting motility indexes [106 ± 13 arbitrary units (a.u.)], compared with CD participants (70 ± 8 a.u.; P  ≤ 0.05). Postprandial small-bowel water content showed a significant time by group interaction ( P  < 0.05), with CD participants showing higher levels from 210 min postprandially. Fasting concentrations of GLP-1 and PYY were significantly greater in CD participants, compared with HVs [GLP-1, CD 50 ± 8 µg/mL versus HV 13 ± 3 µg/mL ( P  ≤ 0.0001); PYY, CD 236 ± 16 pg/mL versus HV 118 ± 12 pg/mL ( P  ≤ 0.0001)]. The meal challenge induced a significant postprandial increase in aversive symptom scores (fullness, distention, bloating, abdominal pain, and sickness) in CD participants compared with HVs ( P  ≤ 0.05). Conclusions: The decrease in fasting small-bowel motility noted in CD participants can be ascribed to the increased fasting gut peptides. A better understanding of the etiology of aversive symptoms in CD will facilitate identification of better therapeutic targets to improve nutritional status. This trial was registered at clinicaltrials.gov as NCT03052465.